Elimination of the blinding effect in landscape luminaires - Ashryatov, Albert; Churakova, Dinara (International Journal of Engineering and Technology, 2018)
The article presents one of the possible options for implementing the lighting technology "Flat beam" for landscape lighting purposes. One of the possible ways to control the light distribution of a number of light sources based on LEDs with different radiation patterns is considered. As a secondary optics, it is proposed to use a mirror surface that redistributes the light flux of an LED light source. It is indicated that, depending on the initial type of the light-emitting diodes light curve and the features of mounting the mirror surface, the resulting light distribution can vary widely, depending on the initial task that the designer sets for himself.Â Â